Biogeochemical context impacts seawater pH changes resulting from atmospheric sulfur and nitrogen deposition. Issue 3 (7th February 2014) - Hagens, Mathilde; Hunter, Keith A.; Liss, Peter S.; Middelburg, Jack J.
Abstract Seawater acidification can be induced both by absorption of atmospheric carbon dioxide (CO2) and by atmospheric deposition of sulfur and nitrogen oxides and ammonia. Their relative significance, interplay, and dependency on water column biogeochemistry are not well understood. Using a simple biogeochemical model we show that the initial conditions of coastal systems are not only relevant for CO2‐induced acidification but also for additional acidification due to atmospheric acid deposition. Coastal areas undersaturated with respect to CO2 are most vulnerable to CO2‐induced acidification but are relatively least affected by additional atmospheric deposition‐induced acidification. In contrast, the pH of CO2‐supersaturated systems is most sensitive to atmospheric deposition. The projected increment in atmospheric CO2 by 2100 will increase the sensitivity of coastal systems to atmospheric deposition‐induced acidification by up to a factor 4, but the additional annual change in proton concentration is at most 28%.